Pengaruh Permainan Bisik Berantai Terhadap Kemampuan Kecerdasan Verbal Linguistik Anak Usia 5-6 Tahun Di TK Pelangi Kasih Siborongborong - Mesiana Sihombing; Emmi Silvia Herlina; Adiani Hulu; Julita Herawati P; Winarti Agustina (Jurnal Pendidikan Agama dan Teologi, 2023)
The aim of this research is to determine the effect of the Chain Whisper Game on the Linguistic Verbal Intelligence Ability of Children Aged 5-6 Years at Pelangi Kasih Siborongborong Kindergarten. The method used in this research is a descriptive quantitative research method. The population was all children aged 5-6 years at Pelangi Kasih Siborongborong Kindergarten, totaling 54 people and a sample of 28 people was determined using a purposive sampling technique. Data was collected using a 25-item positive closed questionnaire. The results of data analysis show that there is a positive and significant influence of the Chain Whisper Game on the Linguistic Verbal Intelligence Ability of Children Aged 5-6 Years at Pelangi Kasih Siborongborong Kindergarten: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.532 > rtable (=0.05,n=28) = 0.374, thus it is known that there is a positive relationship between variable n-2=26)= 2.056, thus there is a significant relationship between variable = "18.54"+0.44X. Thus Ha is accepted and H0 is rejected.